2016
DOI: 10.3945/an.115.009753
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Patterns and Blood Pressure in Adults: A Systematic Review and Meta-Analysis of Randomized Controlled Trials

Abstract: Hypertension is a major risk factor for developing cardiovascular disease, stroke, and kidney disease. To lower blood pressure (BP), several lifestyle changes are recommended such as weight loss, exercise, and following a healthy diet. Investigating the effect of single nutrients may have positive results, but food is consumed as part of a whole diet, resulting in nutrient interactions. The aim of this systematic review and meta-analysis was to assess the effect of dietary patterns on BP in adults. Studies tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

17
169
3
17

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 280 publications
(222 citation statements)
references
References 67 publications
17
169
3
17
Order By: Relevance
“…Surprisingly, greater adherence to the 'fat & sugar' DP was associated with lower systolic blood pressure. These results were not consistent with the current knowledge on this topic [39]. However, subjects in Q4 of the 'fat & sugar' DP, despite similar BMI and waist circumference and lower sodium intake, were younger (P=0.0006) and had higher physical activity level (P < 0.0001) than subjects in Q1, which may partially explain the observed relationships.…”
Section: Discussioncontrasting
confidence: 73%
“…Surprisingly, greater adherence to the 'fat & sugar' DP was associated with lower systolic blood pressure. These results were not consistent with the current knowledge on this topic [39]. However, subjects in Q4 of the 'fat & sugar' DP, despite similar BMI and waist circumference and lower sodium intake, were younger (P=0.0006) and had higher physical activity level (P < 0.0001) than subjects in Q1, which may partially explain the observed relationships.…”
Section: Discussioncontrasting
confidence: 73%
“…Dietary patterns such as the DASH diet [19], the Mediterranean diet [21] and the Nordic diet [41] have been shown to reduce BP. In our previous research, a meta-analysis of 17 randomized controlled trials showed that a dietary pattern that was rich in fruits, vegetables, wholegrains, legumes, nuts, seeds, dairy and fish and low in processed foods and red meat reduced SBP and DBP by 4.06 mmHg and 2.30 mmHg, respectively [42]. In the current study, a diet that was high in nuts, seeds, fruit and fish was associated with lower BP and therefore our findings are consistent with previous research.…”
Section: Discussionmentioning
confidence: 99%
“…Analysing the association between overall dietary pattern and health outcomes is becoming more common as it may account for cumulative and interactive effects and control for dietary confounding (11) . However, the association between overall dietary patterns and hypertension has not been thoroughly studied and the findings are inconclusive (2,10,(12)(13)(14) . Diet is largely determined by regional food availability, culture and distribution.…”
mentioning
confidence: 99%
“…As well, low intakes of vegetable protein (3) , Mg (4) , P (5) and PUFA (6) , and higher intakes of soft drinks (7) , cholesterol (8) , animal protein (3) and red meat (9) , have also been shown to be related to hypertension. Accumulating evidence from randomized clinical trials has shown that vegetarian diets, and those low in saturated animal fat and high in dietary fibre such as the Dietary Approaches to Stop Hypertension (DASH) diet, can effectively lower blood pressure (2,10) . Analysing the association between overall dietary pattern and health outcomes is becoming more common as it may account for cumulative and interactive effects and control for dietary confounding (11) .…”
mentioning
confidence: 99%